Estimasi Parameter Genetik Sifat Pertumbuhan Kambing Boerawa di Kabupaten Tanggamus Propinsi Lampung (Genetic Parameters Estimation on Growth Traits of Boerawa Goat at Tanggamus Regency Lampung Province) - Veronika Yuneriati Beyleto; Sumadi (Sumadi); Tety Hartatik (Buletin Peternakan, 2010)
This research was conducted to estimate heritability, repeatability and genetic correlation values on growth traits of Boerawa goat at Sumber Rejeki farmer group at Campang Village, Gisting District and Karya Makmur I and Karya Makmur II farmer group at Wonoharjo and Sukoharjo Village, Sumber Rejo District, Tanggamus regency, Lampung province. Data consisted of production record and 238 Boerawa goat derived from 93 PE and 7 Boer buck.The research was started on October 30, 2009 up to January 30, 2010. The results indicated that heritability value of birth weight, weaning weight, yearling weigth, average of preweaning daily gain, and average of postweaning weightanalyzed by paternal half-sibs correlation were 0.80±0.40; 0.30±0.17; 0.80±0.04; 0.32±0.18 and 0.30±0.17, respectively. The repeatability values of birth weight, weaning weight and yearling weight analyzed based on tworecording per every dam were 0.42±0.07; 0.32±0.08; 0.30±0.08; 0.30±0.08 and 0.53±0.06. The genetic correlation values among birth weight and weaning weight, birth weight and yearling weight, weaning weight and yearling weight,average of preweaning weight and postweaning weight daily gain analyzed by paternal half-sibs correlation were 0.50±0.04; 0.44±0.08; 0.21±0.03 and 0.20±0.05, respectively. The result also indicated that the heritability andrepeatability values was high and the genetic correlation values were moderate to high.(Key words: Boerawa goat, Genetic parameter, Growth character)